The Optimisation of Routine Paediatric CT Scanning Protocols - Al-Mahrooqi, Khalid Mohammed Salim (Curtin University, 2015)
This study represents one of the first comprehensive paediatric optimisation processes that were systematically approached via three main objectives. It is expected that the devised optimisation paediatric protocols could have profound implications on clinical practices that use 64-slice CT or greater. The study provides a better understanding of the influence of each acquisition reconstruction parameter with regards to image quality and radiation dose during routine paediatric imaging protocols.